2020
DOI: 10.3389/fcell.2020.00189
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Development and T-Dependent Antibody Response Are Regulated by p38γ and p38δ

Abstract: p38MAP kinase (MAPK) signal transduction pathways are important regulators of inflammation and the immune response; their involvement in immune cell development and function is still largely unknown. Here we analysed the role of the p38 MAPK isoforms p38γ and p38δ in B cell differentiation in bone marrow (BM) and spleen, using mice lacking p38γ and p38δ, or conditional knockout mice that lack both p38γ and p38δ specifically in the B cell compartment. We found that the B cell differentiation programme in the BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…p38α (called p38) has been a therapeutic target in CD treatment, but these treatments have not progressed beyond phase I/II clinical trials [ 2 ]. Interestingly, the less studied p38γ and p38δ (p38γ/p38δ) are essential in the immune response and regulate inflammatory molecule production [ 2 , 3 , 4 , 5 , 6 ]. Moreover, the importance of p38γ/p38δ in CRC development has been established in vitro and in an azoxymethane‐dextran sodium sulfate (AOM‐DSS)‐induced CAC model using p38γ/p38δ‐knockout mice [ 2 , 5 ].…”
Section: Figurementioning
confidence: 99%
“…p38α (called p38) has been a therapeutic target in CD treatment, but these treatments have not progressed beyond phase I/II clinical trials [ 2 ]. Interestingly, the less studied p38γ and p38δ (p38γ/p38δ) are essential in the immune response and regulate inflammatory molecule production [ 2 , 3 , 4 , 5 , 6 ]. Moreover, the importance of p38γ/p38δ in CRC development has been established in vitro and in an azoxymethane‐dextran sodium sulfate (AOM‐DSS)‐induced CAC model using p38γ/p38δ‐knockout mice [ 2 , 5 ].…”
Section: Figurementioning
confidence: 99%
“…Moreover, multiple studies investigating the APC function of B cells showed that B cell-derived cytokines contribute to T cell profile skewing, such as T helper (T H ) 1 or T H 2 (39,40). Most B cells, however, are activated via T cell-independent (TI) or T cell-dependent (TD) mechanisms (41). During T cellindependent (TI) B cell activation, antigens with repetitive epitopes, such as polysaccharides, bind to the BCR, resulting in BCR crosslinking (42).…”
Section: B Cell Developmentmentioning
confidence: 99%
“…Proliferation indexes were obtained with FlowJo analysis software (BD Biosciences), showing the ratio of the total number of divisions between the number of cells that went into division. For B-cell proliferation assays, we followed the described method [63]. Briefly, CTV-labelled CD19 + B cells were cultured with goat anti-BCR (20 μg/mL; Jackson Immunoresearch, Ely, UK) plus recombinant mouse IL-4 (20 ng/mL Peprotech, London, UK), and after 96 h, cells were analyzed by flow cytometry and proliferation indexes obtained using FlowJo analysis software.…”
Section: In Vitro Cell Proliferation and T-independent Immunization A...mentioning
confidence: 99%
“…Briefly, CTV-labelled CD19 + B cells were cultured with goat anti-BCR (20 μg/mL; Jackson Immunoresearch, Ely, UK) plus recombinant mouse IL-4 (20 ng/mL Peprotech, London, UK), and after 96 h, cells were analyzed by flow cytometry and proliferation indexes obtained using FlowJo analysis software. For T-independent immunization assays, groups of four control and ICAP-1-null mice were immunized with TNP-Ficoll (Biosearch Technologies) as described in Ref, [63]. Peripheral blood samples were taken 24 h before immunization, and at days 7, 14, and 21 postimmunization.…”
Section: In Vitro Cell Proliferation and T-independent Immunization A...mentioning
confidence: 99%